2021
DOI: 10.21203/rs.3.rs-732454/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-amplification of Oxidative Stress With Tumour Microenvironment-activatable Iron-doped Nanoplatform for Targeting Hepatocellular Carcinoma Synergistic Cascade Therapy and Diagnosis

Abstract: Background: Hepatocellular carcinoma (HCC) is insensitivity to chemotherapy drugs and conventional chemotherapy has long been regarded as ineffective against HCC. Ferroptosis is a form of programmed cell death with a definite Fenton reaction mechanism that converts endogenous hydrogen peroxide (H2O2) into highly toxic hydroxyl radicals (·OH), expected to inhibit HCC in cooperation with chemotherapy.Methods: The organic/inorganic nanoplatform were characterized by various methods to analyze the morphology, elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Doxorubicin (DOX) is a cytotoxic anthracycline antibiotic, widely used for treating a variety of cancers, which is considered as the foundation of chemotherapy for breast cancer (40). Accumulating studies have shown that doxorubicin promoted cancer cell death through inhibiting DNA replication and generating H 2 O 2 , which is the Fenton reaction substrate leading to increased ROS production (41, 42). Thus, doxorubicin might kill cancer cells by indirectly inducing ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Doxorubicin (DOX) is a cytotoxic anthracycline antibiotic, widely used for treating a variety of cancers, which is considered as the foundation of chemotherapy for breast cancer (40). Accumulating studies have shown that doxorubicin promoted cancer cell death through inhibiting DNA replication and generating H 2 O 2 , which is the Fenton reaction substrate leading to increased ROS production (41, 42). Thus, doxorubicin might kill cancer cells by indirectly inducing ferroptosis.…”
Section: Discussionmentioning
confidence: 99%